A method to remove the influence of fixative concentration on postmortem T2 maps using a kinetic tensor model. Issue 18 (20th September 2021) - Tendler, Benjamin C.; Qi, Feng; Foxley, Sean; Pallebage‐Gamarallage, Menuka; Menke, Ricarda A. L.; Ansorge, Olaf; Hurley, Samuel A.; Miller, Karla L.
Abstract: Formalin fixation has been shown to substantially reduce T2 estimates, primarily driven by the presence of fixative in tissue. Prior to scanning, post‐mortem samples are often placed into a fluid that has more favourable imaging properties. This study investigates whether there is evidence for a change in T2 in regions close to the tissue surface due to fixative outflux into this surrounding fluid. Furthermore, we investigate whether a simulated spatial map of fixative concentration can be used as a confound regressor to reduce T2 inhomogeneity. To achieve this, T2 maps and diffusion tensor estimates were obtained in 14 whole, formalin‐fixed post‐mortem brains placed in Fluorinert approximately 48 hr prior to scanning. Seven brains were fixed with 10% formalin and seven brains were fixed with 10% neutral buffered formalin (NBF). Fixative outflux was modelled using a proposed kinetic tensor (KT) model, which incorporates voxelwise diffusion tensor estimates to account for diffusion anisotropy and tissue‐specific diffusion coefficients. Brains fixed with 10% NBF revealed a spatial T2 pattern consistent with modelled fixative outflux. Confound regression of fixative concentration reduced T2 inhomogeneity across both white and grey matter, with the greatest reduction attributed to the KT model versus simpler models of fixative outflux. No such effect was observed in brains fixed with 10% formalin. Correlations between the transverse relaxation rate R 2 and ferritin/myelin proteolipid protein (PLP) histology lead to an increased similarity for the relationship between R 2 and PLP for the two fixative types after KT correction. Abstract : Fixed post‐mortem tissue samples are often placed into a fluid with more favourable imaging properties prior to MRI scanning. This study investigates whether there is evidence for a change in T2 in regions close to the tissue surface due to fixative outflux into this surrounding fluid, and whether a simulated spatial map of fixative concentration can be used as a confound regressor to reduce T2 inhomogeneity. Modelling fixative outflux using a proposed kinetic tensor (KT) model, we identified a spatial T2 pattern consistent with modelled fixative outflux, and demonstrated that regressing fixative concentration reduced T2 inhomogeneity across both white and grey matter in brains fixed with 10% neutral buffered formalin (NBF).